2015
DOI: 10.1063/1.4919374
|View full text |Cite
|
Sign up to set email alerts
|

Vortex polarity switching in magnets with surface anisotropy

Abstract: Vortex core reversal in magnetic particle is essentially influenced by a surface anisotropy. Under the action of a perpendicular static magnetic field the vortex core undergoes a shape deformationof pillow-or barrel-shaped type, depending on the type of the surface anisotropy. This deformation plays a key point in the switching mechanism: We predict that the vortex polarity switching is accompanied (i) by a linear singularity in case of Heisenberg magnet with bulk anisotropy only and (ii) by a point singularit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…4(i). Note, that a similar shape distortion is observed for vortices in easy-plane ferromagnets with surface anisotropy [66,67].…”
Section: Skyrmionsupporting
confidence: 65%
“…4(i). Note, that a similar shape distortion is observed for vortices in easy-plane ferromagnets with surface anisotropy [66,67].…”
Section: Skyrmionsupporting
confidence: 65%
“…While many of the aforementioned effects have been investigated mostly in bulk or in flat thin-film samples, over the last decade, curvature induced effects have been uncovered as a new way to manipulate magnetic equilibria as well as spin dynamics. Numerous theoretical and numerical works have already shown that the surface curvature of magnetic membranes leads to phenomena which are not present in flat geometries of the same material [19][20][21][22][23][24][25][26][27][28]. As a result of the bending, in conventional soft magnetic materials exotic non-collinear magnetic textures such as skyrmions [29] may be stabilized or magnetisation dynamics can be influenced, leading to left-right symmetry breaking of domain wall motion [19,20], asymmetric spin-wave transport [25,30] or the emergence of a topological Berry phase [31].…”
mentioning
confidence: 99%